(untitled) (Heritage, 2021)
The paper examines the characteristics of the orthography of Resava in the Baranja Transcription of Dušan’s Code, created at the beginning of the 16 ͭ ͪ century. The research included the following features: the writing of the grapheme x, the writing of the grapheme Q at the etymological place, the use of the grapheme J in front of j, the use of the ligature ] to mark the initial group [ja] and the use of the grapheme a to mark the aforementioned group after a vowel, the use of the graphemes e and j to mark the group [je] in all positions in the word, the use of the Greek letters, the latest punctuation system, and, lastly, the writing of the accents and spiritus lenis. A significant number of examples confirmed the use of the grapheme Q at the etymological place, the use of the grapheme J to mark the so-called reduced i, the use of the grapheme a to write the group [ja] after a vowel, the use of the comma and the full stop on the line on the bottom, as well as the writing of the accents and spiritus lenis. The research has also shown that the grapheme x was written in an isolated example, that the group [je] was primarily written by using graphemes j and e, which is in accord with the orthography of Resava, and, finally, that the rare use of the Greek letters is related to the Greek words. Therefore, it was concluded that the norms of the orthography of Resava were not consistently implemented in the Baranja Transcription of Dušan’s Code. The research also confirmed the coexistence of Raška and Resava orthographic norms in some cases.